Antioxidant, anti-inflammatory and hepatoprotective activities on carbon tetrachloride - induced hepatic damage in mice of trang to (ixora duffii) leaf extract - Dinh, Phan Kim; Tuan, Nguyen Trong; Trang, Dai Thi Xuan (Academia Journal of Biology, 2019)
Trang To (Ixora duffii) belongs to the genus Ixora in the family Rubiaceae. The in vitro total antioxidant and anti-inflammatory capacity of the methanol extract of Trang To leaf was investigated using the phosphomolypdenum method and the bovine serum albumin denaturation test, respectively. The results showed that the methanol extract of Trang To leaf possessed relatively high antioxidant activity (OD0,5 = 15,551 ± 0,344 μg/mL) compared to that of the standard, trolox (OD0,5=2,315±0,083 μg/mL). The anti-inflammatory effect using bovine serum albumin denaturation test showed that the activity of the methanol extract of Trang To leaf (EC50= 6,03±0,12 μg/mL) was comparable to that of the reference drug, diclofenac sodium (EC50=0,57±0,21µg/mL). To evaluate the hepatoprotective activity of the methanol extract of Trang To leaf, the liver damage was induced in mice given with carbon tetrachloride (CCl4) mixed in olive oil (1: 4) at a dose of 2.5 mL/kg body weight/day. As a control, the standard hepatoprotective agent, silymarin, was used at the dose of 16 mg/kg body weight for 4 consecutive weeks. Trang To leaf extract was given at three different doses 100, 200 and 400 mg/kg body weight. The results showed the effective dose-dependent reduction of transaminase enzyme (ALT and AST) levels in sera. In addition, Trang To leaf extract also improved the oxidative stress status of the liver through effective reduction of MDA level and increase of GSH level in the liver. Histopathological examination of the liver tissue revealed that the mice treated with Trang To leaf extract showed significant improvement of liver tissue damages similar to silymarin treatment compared to the non-treated control group. The present results demonstrated that Trang To leaf extract has potent antioxidant and hepatoprotective activity.